Gap Dromions and Domain Walls with Dispersive Reflectivity Having Cubic-Quintic-Septic-Nonic Self-Phase Modulation in Presence of Multiplicative White Noise - Zayed, E. M. E.; Alurrfi, Khaled A. E.; Ahmed, Manar S.; Arnous, Ahmed H.; Yildirim, Yakup; Moraru, Luminita; Mahmood, Amer Shaker; Chaloob, Ibrahim Zegalhaiton; Mohammed, Farag Mahel; Biswas, Anjan (Contemporary Mathematics, 2025)
This paper is about the retrieval of gap dromions in the presence of multiplicative white noise. The self-phase modulation exhibits a cubic–quintic–septic–nonic structure. Two integration approaches retrieve the dromions and domain walls, namely, the enhanced direct algebraic approach and the addendum to Kudryashov’s scheme. The obtained solutions are subsequently classified.